Intraarterial Thrombolysis for Treatment ofAcute Stroke: Experience in 26 Patients withLong-Term Follow-up - Jahan, Reza; Duckwiler, Gary R.; Kidwell, Chelsea S.; Sayre, James W.; Gobin, Y. Pierre; PabloVillablanca, J.; Saver, Jeffrey; Starkman, Sidney; Martin, Neil; Vinuela, Fernando (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Since the approval of intravenous tissue plasminogen activator for acute ischemic stroke, great interest has been generated in cerebral fibrinolysis. Our purpose was to assess long-term outcome and hemorrhagic risk in patients with anterior circulation ischemic stroke treated with intraarterial urokinase.METHODS: Twenty-six patients were treated within 6 hours of ictus; of these, 21 were followed up for an average of 23 months. Angiographic reperfusion was classified according to thrombolysis in myocardial infarction (TIMI) grades. The Rankin Scale (RS) and the modified Barthel Index (mod BI) were used as outcome measures (good outcome: RS = 0–2, mod BI = 16–20; poor outcome: RS = 3–5, mod BI ≤ 15).RESULTS: Ten of the 21 patients (average age, 48 years) had a good outcome; three (average age, 71 years) had a poor outcome; eight patients (average age, 78 years) died. Partial/complete (successful) recanalization was observed in 11 of 26 patients and minimal or no (unsuccessful) recanalization in 15. Recanalization favored a better outcome: nine of 21 had successful recanalization, with a good outcome in seven; 12 of 21 had unsuccessful reperfusion, with poor outcome/death in nine. Poor outcome was noted in five patients with internal carotid artery (ICA) bifurcation occlusions, four of whom had unsuccessful recanalization and poor outcome or death. Hemorrhage occurred in 10 of the 26 patients, with clinical deterioration in three. The average dose of urokinase was higher in the hemorrhage group, and mortality was higher in patients who hemorrhaged.CONCLUSION: Intraarterial thrombolysis is feasible in the setting of acute stroke. Successful reperfusion is associated with a better outcome, and the prevalence of hemorrhage does not exceed that which occurs in the natural history of embolic stroke. Poor outcome or death is associated with nonrecanalization, older age, hemorrhage, and ICA bifurcation occlusions.